2011
DOI: 10.1177/0956797611411586
|View full text |Cite
|
Sign up to set email alerts
|

Self-Regulation of Priming Effects on Behavior

Abstract: In three experiments, we tested whether people can protect their ongoing goal pursuits from antagonistic priming effects by using if-then plans (i.e., implementation intentions). In Experiment 1, concept priming did not influence lexical decision time for a critical stimulus when participants had formed if-then plans to make fast responses to that stimulus. In Experiment 2, participants who were primed with a prosocial goal allowed a confederate who asked for help to interrupt their work on a focal task for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 33 publications
2
46
0
Order By: Relevance
“…Affirming a social value may have primed alcohol-related behaviour (Friedman et al, 2009). However, forming an implementation intention can disrupt goal-priming effects on behaviour (Gollwitzer, Sheeran, Trštschel, & Webb, 2011;Webb, Sheeran, Gollwitzer, & Trštschel, 2012). Students who formed an implementation intention…”
Section: Self-affirmation and Implementation Intentionsmentioning
confidence: 99%
“…Affirming a social value may have primed alcohol-related behaviour (Friedman et al, 2009). However, forming an implementation intention can disrupt goal-priming effects on behaviour (Gollwitzer, Sheeran, Trštschel, & Webb, 2011;Webb, Sheeran, Gollwitzer, & Trštschel, 2012). Students who formed an implementation intention…”
Section: Self-affirmation and Implementation Intentionsmentioning
confidence: 99%
“…This strategy comprises planning accomplishment of intentions through specification of when, where and how the actions to accomplish the desired behavior (5)-individuals who fulfill these instructions are more favorable to initiate and maintain the behavior-setting the formulation of a specific plan seems to be a promising way to translate intention into action. Additionally, a meta-analysis indicated that action plans/implementation intentions had an overall effect size of 0.65 on goal attainment (7) .…”
Section: Introductionmentioning
confidence: 99%
“…However, Bargh et al (2010) suggested that when conscious and nonconscious goals conflict with each other, the conscious goal prevails and directs behavior (cf. Gollwitzer, Sheeran, Trö tschel, & Webb, 2012). For instance, MacRae and Johnston (1998) primed half of their participants with helpfulness and the other half were not primed.…”
Section: Discussionmentioning
confidence: 94%